Inequality and growth: Marxian and post-Keynesian/Kaleckian perspectives on distribution and growth regimes before and after the Great Recession - Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
The re-distribution of income from labour to capital, from workers to top-managers, and from low income households to the rich has been an important feature of financedominated capitalism since the early 1980s. After the Great Financial Crisis and the Great Recession in 2007-9, the recovery has been sluggish so far, and this has given rise to a renewed discussion about stagnation tendencies in capitalist economies. In orthodox approaches income distribution only has a restricted role to play, if at all, but the interaction between distribution and growth is at the centre of Marxian and post-Keynesian/Kaleckian approaches when it comes to explaining medium- to long-run trends of economic growth - and stagnation. In this contribution we will thus provide Marxian and Kaleckian assessments of the distribution and growth regimes under finance-dominated capitalism, both before and after the recent crisis. Finally, we also sketch an interpretation of stagnation tendencies in a demand-led endogenous growth model with Kaleckian, Kaldorian and Marxian features.
Keywords: E11; E21; E22; E25; E60; F43; F62; O40; 330; distribution; growth; financialisation; stagnation; macroeconomic demand and growth regimes; productivity growth; Kaleckian models; Marxian models